2010
DOI: 10.1103/physrevb.81.184301
|View full text |Cite
|
Sign up to set email alerts
|

Ionic conductivity of nanocrystalline yttria-stabilized zirconia: Grain boundary and size effects

Abstract: We report on the effect of grain size on the ionic conductivity of yttria-stabilized zirconia samples synthesized by ball milling. Complex impedance measurements, as a function of temperature and frequency are performed on 10 mol % yttria-stabilized zirconia nanocrystalline samples with grain sizes ranging from 900 to 17 nm. Bulk ionic conductivity decreases dramatically for grain sizes below 100 nm, although its activation energy is essentially independent of grain size. The results are interpreted in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 51 publications
3
46
3
Order By: Relevance
“…12 It was reported that the conductivity associated to oxide ions traveling through the grain-boundary core from one grain to another one is similar for samples with grain sizes ranging from ∼1 μm to 17 nm, i.e., it is rather independent of the grain size (see Fig. 1, right axis).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…12 It was reported that the conductivity associated to oxide ions traveling through the grain-boundary core from one grain to another one is similar for samples with grain sizes ranging from ∼1 μm to 17 nm, i.e., it is rather independent of the grain size (see Fig. 1, right axis).…”
Section: Introductionmentioning
confidence: 84%
“…More details about sample preparation and characterization were reported in previous works. 12,13 The mechanically alloyed sample is labeled as MA, and sintered samples as MA-1350, MA-950, MA-850, and MA-750, where the number indicates the sintering temperature. In addition we have also studied commercial powders of 10% mol YSZ (Tosoh-Europe), 5.4% mol YSZ (Alfa Aesar), and ZrO 2 (Alfa Aesar), hereafter labeled C-10, C-5, and C-Zr respectively.…”
Section: Experiments and Computation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation resembles that of Durá et al [36] who studied oxygen ion conductivity in nanostructured ZrO 2 . The authors presented indications of an extended space-charge layer because of oxygen vacancy segregation in the grain-boundary core region.…”
Section: Conductivity Measurementsmentioning
confidence: 53%
“…Conductivities in the mS range at room temperature [34,35]. Space-charge and segregation effects might be used to explain the decrease in ionic conductivity when going from single crystals to nm-sized systems with high surface areas [36]. [34] would translate into very fast F exchange processes as reported for single crystals.…”
Section: Conductivity Measurementsmentioning
confidence: 99%